Some aspects of clinical trial of the drug "Vetmicoderm" - Ogloblina, M. V.; Bushueva, I. V.; Martynyshyn, V. P.; Hunchak, V. M.; Parchenko, V. V.; Бушуєва, Інна Володимирівна; Парченко, Володимир Володимирович (My University, 2024)
Our aim was to conduct some clinical trials of the drug «Vetmikoderm» and compare its effectiveness with the well-known agent «Triosan». Clinical trials to determine the therapeutic effectiveness of the drug «Vetmikoderm» were carried out at the veterinary clinic «BEST» (Zaporizhzhia) on two groups of dogs, formed by gradual recruitment (based on the owners' referral to the clinic). To determine the etiological factors contributing to the development of dermatosis, we conducted a study of skin microflora. The sensitivity of microorganisms and fungi to the action of the «Vetmikoderm» preparation was determined by the disc-diffusion method. In the process of diagnostic research, including microbiological studies, it was established that conditionally pathogenic microflora from affected areas of dogs' skin was represented by both microorganisms and fungi. At the same time, fungi prevailed in the microbiocenosis of the selected skin samples. It is worth noting that «Vetmikoderm» has a better fungicidal effect, while «Triosan» is evidently more effective in treating dermatoses with predominantly microbial contamination. It has been proven that the combined use of both drugs has a better influence on the recovery process in animals.
Keywords: 1,2,4-triazoles; Skin diseases of fungal etiology; Sensitivity of microorganisms; Fungi; Clinical studies; Vetmikoderm; Triosan